Management of a child with reactive attachment disorder in the dental clinical setting : a case report = Manejo de un niño con trastorno de apego reactivo en el entorno clínico dental : reporte de un caso - Garrocho Rangel, Arturo 1961-; Romero Huízar, Hilda; Ruiz Rodríguez, Socorro 1965-; Campos Lara, Nadia P.; Pozos Guillén, Fernando (2020)
Reactive attachment disorder (RAD) is an early childhood mental health disease characterized by impaired social interactions and communication abilities, and neurological deficits in the child's developing brain. This disorder can significantly affect the pediatric patient's behavior in the dental setting. An uncooperative 9-year-old Mexican girl, who was residing in a temporary home, was referred by a general dental practitioner to the Postgraduate Pediatric Dental Clinic with her caretaker, requesting dental examination and treatment. The patient presented with a previous diagnosis of RAD with intellectual/social disability. With the psychiatrist's guidance, an exhaustive oral prophylaxis was carried out in the initial appointments, followed by diverse restorative treatments under the continuous application of behavioral management techniques. These restorative procedures included resin restorations and pit-fissure sealants, under local anesthesia and rubber-dam isolation, on the first four permanent molars. The entire treatment was completed in six weeks. The patient and her caretaker were provided with detailed educational and motivational strategies for improving the patient ́s oral hygiene, and they also received nutritional advice. For control reviews and the reinforcement of preventive habits, future appointments were carefully scheduled. An interdisciplinary pediatric collaboration between the dentist, nurse, and psychiatrist was fundamental for improving the patient's oral health and general welfare.
El trastorno de apego reactivo (RAD, por sus siglas en inglés) es una enfermedad de salud mental en la primera infancia caracterizada por interacciones sociales y capacidades de comunicación deterioradas y por déficits neurológicos en el cerebro en desarrollo del niño. Este trastorno puede afectar significativamente el comportamiento del paciente pediátrico en el entorno dental. Una niña mexicana de 9 años de edad, poco cooperadora, que residía en un hogar temporal, fue remitida a la Clínica de Odontología Pediátrica con su cuidadora, solicitando un examen y tratamiento dental. La paciente presentó un diagnóstico previo de RAD con discapacidad intelectual/social. Con la orientación del Psiquiatra, se llevó a cabo una profilaxis oral exhaustiva en las citas iniciales, seguidas de diversos tratamientos de restauración bajo la aplicación continua de técnicas de manejo del comportamiento. Estos procedimientos de restauración incluyeron restauraciones de resina y selladores de fosas y fisuras, bajo anestesia local y aislamiento con dique de goma, en los primeros cuatro molares permanentes. Todo el tratamiento se completó en seis semanas. La paciente y su cuidadora recibieron estrategias educativas y motivacionales detalladas para mejorar la higiene oral y también recibieron asesoría nutricional. Para las revisiones de control y refuerzo de los hábitos preventivos, las citas posteriores se programaron cuidadosamente. Una colaboración pediátrica interdisciplinaria entre el dentista, la enfermera y el psiquiatra fue fundamental para mejorar la salud oral y el bienestar general del paciente.
En revista Odóvtos, vol. 22, no. 1 (enero-abril 2020)
Descripción basada en el contenido visto el 26 de septiembre, 2024
También disponible en formato HTML y EPUB
Keywords: ODONTOLOGIA INFANTIL; TRASTORNOS DE LA CONDUCTA INFANTIL; APEGO EN NIÑOS; CONDUCTA DEPENDIENTE